On the relationship between pH-dependent β-lactoglobulin self assembly and gelation dynamics - Martinez, María Julia (2018)
There are a lot of works in literature about the size particle of β-lactoglobulin (β-lg) at different conditions and also about its rheological properties; however, there are not works which connect both results. The aim of this work was precisely to relate the state of association of β-lg in solution with the heat-induced aggregation and the dynamics of gelation upon heating in a wide range of pH. The state of association and the heat-induced aggregation of β-lg were evaluated by the determination of its size particle at room temperature and upon heating by dynamic light scattering, while the dynamics of gelation was studied by rheological measurements in a controlled stress rheometer. The state of association of β-lg was highly dependent on pH at room temperature increasing near to its isoelectric point. The rate of heat aggregation, the size of aggregates and the dynamic of gelation of β-lg were also highly dependent on pH. Finally, a mechanism involved in β-lg gelation at different pH values is proposed. The dynamic light scattering technique proved to be a useful tool to characterize the state of association and the onset of β-lg aggregation upon heating for understanding the behaviour of these proteins, for example, under the effect of heating on the gelling properties.